Spin-phonon coupling and magnetoelectrical properties: EuMnO3 versus GdMnO3 - Ferreira, W. S. (2009)
Correlation between spin-phonon coupling and the magnetoelectric properties of EuMnO3 and GdMnO3 were investigated using ceramic samples in this work. The experimental results evidence a stronger spinphonon coupling in GdMnO3 than in EuMnO3, as well as a clear anomaly in the phonon contribution for the dielectric constant. This anomaly is located at the paramagnetic-incommensurate antiferromagnetic phasetransition temperature of GdMnO3, corroborating the existence of a magnetoelectric effect in this system. The absence of the magnetoelectric effect in EuMnO3 is due to the existing disorder revealed in this compound by the striking thermal metastability and the large decrease in the activation energy associated with the dielectric relaxation processes. This kind of behavior has no counterpart in GdMnO3. In fact, it has been confirmed that the existence of spin-phonon coupling is not a sufficient condition for the existence of magnetoelectric property, and other mechanisms have to be considered in order to understand the magnetoelectric properties.